THE EFFECT OF EYE TRACKING MOVEMENT TRAINING ON BALANCE ABILITY FOR STROKE PATIENT - Kim, Myeong-Jun; Kim, Tae-Ho (International Journal of Psychosocial Rehabilitation, 2020)
Stroke patients show delay in visual-spatial recognition and visual perception because of neurological deficit. 30 stroke patients were randomly divided into a eye tracking exercise group and a general exercise therapy group for six weeks, eye tracking program is consisting of saccade, optokinetic, vestibulo, eye tracking, and eye fixation. And the results were compared before and after the intervention using a balanced analysis device. There was a statistically significant difference in path length, path velocity, and Area 95% in an eye tracking exercise group compared with general exercise group(p